Total nucleated cell dose in graft is a better prognostic factor for survival in pediatric patients transplanted with bone marrow compared to CD34+, CD3+, or total mononuclear cell count. Issue 1 (25th October 2021) - Kupeli, Serhan; Inan, Gul; Ozkan, Ayse; Sezgin, Gulay; Bayram, Ibrahim; Tanyeli, Atila
Abstract: Background: Most studies investigating the impact of graft composition on transplant‐related outcomes have focused on the effect of CD34+ cell dose and reported equivocal results. The aim of this study is to investigate the impact of doses of total nucleated cells (TNCs), total mononuclear cells (TMCs), CD3+, and CD34+ cells on the outcome of children receiving allogeneic hematopoietic stem cell transplantation (HSCT). Methods: Children and adolescents who underwent allogeneic HSCT for malignant hemato‐oncological diseases or nonmalignant diseases in Cukurova University Faculty of Medicine, Pediatric Bone Marrow Transplantation Center between 2010 and 2020 were enrolled in the study. Results: A total of 212 patients receiving allogeneic HSCT (154 bone marrow transplantation; 58 peripheral blood stem cell transplantation) from matched related or unrelated donors were included in the study. Higher TNC doses associated with a superior 5‐year event‐free survival (EFS; 67.7% vs 44.7%) in the whole group (log‐rank P = .027). Overall survival (OS) and EFS of bone marrow–transplanted patients differed significantly according to TNC doses (log‐rank P = .041 and .027, respectively). Multivariant analysis for OS revealed a P value of .038 for TNC, Exp(B) = 1.939 (95% CI: [1.038, 3.621]). That for EFS revealed a P value of .025 for TNC, Exp(B) = 1.992 (95% CI: [1.088, 3.647]). There was no relationship between doses of CD34+ cells, CD3+ cells, TMC, TNC, and neutrophil or platelet engraftment. Conclusion: Our data suggest that TNC dose is a better prognostic factor for pediatric allogeneic HSCT outcomes than doses of CD34+ cells, CD3+ cells, or TMC in patients transplanted with bone marrow. Future studies analyzing cell subsets and other components in TNC could elaborate the factor(s) accompanying this observed survival advantage.